Intermediate Algebra: Connecting Concepts through Application

Published by Brooks Cole
ISBN 10: 0-53449-636-9
ISBN 13: 978-0-53449-636-4

Chapter 6 - Logarithmic Functions - 6.5 Solving Exponential Equations - 6.5 Exercises: 76

Answer

$k = -0.683, -7.317$

Work Step by Step

$-2(k+4)^{2} + 8 = -14$ $-2[k(k+4)+4(k+4)] = -14 -8$ $-2[k^{2} +4k +4k + 16] = -22$ $-2[k^{2} +8k + 16] = -22$ $-2k^{2} - 16k - 32 = -22$ $-2k^{2} - 16k -32 + 22= 0$ $-2k^{2} - 16k -10= 0$ $-2(k^{2} + 8k + 5) = 0$ $k = \frac{-8±\sqrt {(8)^{2}-4(1)(5)}}{2(1)}$ $k = \frac{-8±\sqrt {64-4(1)(5)}}{2}$ $k = \frac{-8±\sqrt {64-20}}{2}$ $k = \frac{-8±2\sqrt {11}}{2}$ $k = \frac{-4±\sqrt {11}}{1}$ $k = -4±\sqrt {11}$ $k = -0.683, -7.317$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.